RELATIONSHIP BETWEEN VERBAL ABUSE AND SELF-CONFIDENCE ON CHILD AGED SCHOOL AT PABEAN SEDATI SIDOARJO - Farida, Denis; Jayadi, Alpian; Cahyanto, Heri Nur (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: Verbal abuse is a type of verbal abuse that can cause stress and have a negative impact on mental health. Verbal abuse if done continuously to children in the long term will have an impact on self-confidence in children. Objective: The purpose of this study was to determine the relationship between verbal abuse and self-confidence in children in Pabean Village, Sedati District, Sidoarjo. Methods: The method in this research is to use a quantitative type of research with a cross sectional research design. The sample in this study amounted to 36 people. The sampling technique used purposive sampling technique. Data collection using questionnaires and data analysis using the Spearman Rank (Rho) test. Result: The results of the Spearman Rank statistical test obtained (p = 0.000; r = -0.570). The relationship between verbal abuse and self-confidence of school-age children, at Pabean Sidoaarjo has a strong relationship with a negative correlation. Conclusion: The importance of preventing and overcoming verbal abuse in children. This research provides an understanding of the negative impact of verbal abuse on children's self-esteem and reinforces the need to develop approaches that involve protection and recovery for children who have experienced verbal abuse. Measures of protection, education and psychological support should be put in place to ensure the mental and emotional well-being of children in society.